PEMAHAMAN KONSEPTUAL SISWA DALAM MATERI SPLDV BERDASARKAN KEMAMPUAN MATEMATIKA DI KELAS IX - Nurhayati, Nurhayati; Sugiatno, Sugiatno; Ijudin, Romal (Universitas Tanjungpura, 2024)
This study aims to determine the conceptual understanding of students at SMP Negeri 16 Pontianak regarding the material on Systems of Linear Equations in Two Variables (SPLDV) which depends on their mathematical abilities. In this research, nine class IX C students were used as a source of descriptive data. The data collected in this research came from daily tests carried out by students to determine their ability level. The results of the research show that the five indicators of conceptual understanding used indicate that students' conceptual understanding is classified as moderate. These indicators are as follows: (1) students' conceptual understanding of re-explaining SPLDV concepts is in the medium category, (2) students' conceptual understanding of determining examples and non-examples of SPLDV material is in the low category, (3) students' conceptual understanding of grouping objects according to their characteristics are included in the low category, (4) The high category has a conceptual understanding of indicators of use, utilization and selection of procedures in SPLDV material, (5) the medium category has a conceptual understanding of usage indicators and the relationship between models, diagrams and concept representations different in SPLDV material.